2023
DOI: 10.22178/pos.89-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effectiveness of Polymerase Chain Reaction and Microscopy in Malaria Diagnosis

Abstract: Malaria is a life-threatening parasitic disease which causes enormous morbidity and mortality in tropical African countries. Successful prevention and treatment of infected individuals heavenly depend on successful diagnosis using recommended techniques. These routine laboratory techniques have different performance indices. Therefore, this study aimed to evaluate the performance of Polymerase Chain Reaction and Microscopy in malaria diagnosis. A total of two hundred consented study subjects were randomly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…(Okuta et al, 2020). These results are similar to those reported from Nigeria and Cameroon (Muhammad et al, 2022, Nana et al, 2021, which turned out to be significantly higher than what we found in our study. This is because of the small sample sizes in their studies compared to our study, making the positivity rate more susceptible to specific positive or negative cases.…”
Section: Sociodemographic Characteristics Of the Participantssupporting
confidence: 91%
“…(Okuta et al, 2020). These results are similar to those reported from Nigeria and Cameroon (Muhammad et al, 2022, Nana et al, 2021, which turned out to be significantly higher than what we found in our study. This is because of the small sample sizes in their studies compared to our study, making the positivity rate more susceptible to specific positive or negative cases.…”
Section: Sociodemographic Characteristics Of the Participantssupporting
confidence: 91%
“…for HRP2 and PLDH mRDTs, respectively [20]. These results are similar to those reported from Nigeria and Cameroon, which turned out to be significantly higher than what we found in our study [21,22]. This is because of the small sample sizes in their studies compared to our study, making the positivity rate more susceptible to specific positive or negative cases.…”
Section: The Most Common Plasmodium Speciessupporting
confidence: 87%